Factors Associated With Speaking English as a Foreign Language Effectively in Higher Education - Butarbutar, Ranta; Marlina Radja Leba, Seli; ., Marnina; Florensia Sauhenda, Angla (KnE Social Sciences, 2023)
This study aimed to investigate the factors that influence the effective speaking of English as a foreign language (EFL) in higher education. Data were collected through an open-ended, in-depth interview with seven interviewees and analyzed using the thematic analysis (TA) technique. The results showed six significant themes related to effective student speaking: aptitude, motivation, opportunity, learning media, learning strategy, and language function. Future research must collect more diverse instances of effective speaking functions and components. Multiple examples of speaking in many genres developed by demographically diverse students in natural settings will provide more realistic and complete views of schoolchildren’s increasing ability to use nominal expressions to construct and communicate meaning for academic objectives. Keywords: Aptitude, EFL, Higher Education, Speaking Skills